2018
DOI: 10.1111/tpj.13877
|View full text |Cite
|
Sign up to set email alerts
|

CsSPL functions as an adaptor between HDZIP III and CsWUS transcription factors regulating anther and ovule development in Cucumis sativus (cucumber)

Abstract: Anther and ovule genesis preconditions crop fertilization and fruit production; however, coordinative regulation of anther and ovule development and underlying molecular pathways remain largely elusive. Here, we found that SPOROCYTELESS (SPL)/NOZZLE (NZZ) expression was nearly abolished in a Cucumis sativus (cucumber) mutant with severely defective anther and ovule development. CsSPL was expressed specifically in the developing anthers and ovules. Knock-down of CsSPL reduced male and female fertility with malf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…The differentially expressed lncRNAs may affect the female gametophyte by affecting the auxin response. As important transcriptional regulatory elements, transcription factors play crucial roles in the reproductive process of female plants [4446]. In our data, LTCONS_00004164, LTCONS_00070807, LTCONS_00011471, and LTCONS_00042441 were significantly downregulated; LTCONS_00004164 and LTCONS_00070807 targeted two MYB transcription factor genes, Osmyb4 (LOC_Os01g50110) and Osmyb55 (LOC_Os05g48010), respectively, and LTCONS_00011471 and LTCONS_00042441 targeted the two bZIP transcription factor genes OsbZIP09 (LOC_Os01g59760) and OsbZIP24 (LOC_Os02g58670), respectively.…”
Section: Discussionmentioning
confidence: 55%
“…The differentially expressed lncRNAs may affect the female gametophyte by affecting the auxin response. As important transcriptional regulatory elements, transcription factors play crucial roles in the reproductive process of female plants [4446]. In our data, LTCONS_00004164, LTCONS_00070807, LTCONS_00011471, and LTCONS_00042441 were significantly downregulated; LTCONS_00004164 and LTCONS_00070807 targeted two MYB transcription factor genes, Osmyb4 (LOC_Os01g50110) and Osmyb55 (LOC_Os05g48010), respectively, and LTCONS_00011471 and LTCONS_00042441 targeted the two bZIP transcription factor genes OsbZIP09 (LOC_Os01g59760) and OsbZIP24 (LOC_Os02g58670), respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Notably, the aforementioned genes, CsIAA29 , CsCRC , and CsFUL , displayed similar expression trends in a previous study investigating the fruit length in cucumbers ( Jiang et al, 2015 ), thus suggesting that these genes may play pivotal roles in early fruit development. Interestingly, CsSPL , which encodes a protein that directly interacts with CsWUS (WUSCHEL) and positively regulates CsWUS and CsARF3 ( AUXIN RESPONSE FACTOR 3) expression ( Liu et al, 2018 ), showed a 4.4-fold higher expression in M12 and H34. Thus, CsSPL not only regulates sex organ development by interacting with auxin signaling, as recently reported, but may also participate in the process of sex differentiation in cucumbers.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatic methods have enabled the identification of homologues of "vegetative" YABBYs in the genomes of tomato (Solanum lycopersicum L., nine YABBY genes; [54]), apple (Malus pumila Mill., 13 YABBY genes; [66]), Chinese cabbage (Brassica rapa L. ssp. pekinensis; [67]), cucumber (Cucumis sativus L.; [68]), snapdragon (Antirrhinum majus L.; [69,70]), and grape (Vitis pseudoreticulata, two YABBY genes; [71]).…”
Section: "Vegetative" Yabby Genesmentioning
confidence: 99%